College Admissions Tests and LD and ADHD Documentation Guidelines: Consistency With Emerging Legal Guidance. (June 2017) - Lindstrom, Will; Lindstrom, Jennifer H.
Testing agencies request documentation to verify a test-taker's disability status under the Americans With Disabilities Act of 2008 and Section 504 of the Rehabilitation Act of 1973. A number of recent legal developments, culminating in technical assistance from the U.S. Department of Justice, suggest changes in enforcement of relevant laws are imminent. This article reviews the legal developments and presents results of a survey of the learning disability and Attention-Deficit/Hyperactivity Disorder documentation guidelines of 10 standardized tests commonly used to aid admissions decisions for undergraduate and graduate programs. Consistent with the recent guidance, virtually all guidelines requested documentation from a qualified evaluator, a diagnosis, and accommodation recommendations and rationale. In contrast, agencies were less likely to request the information necessary to grant accommodations based on history of accommodation use. Few agencies had policies allowing submission of reduced amounts of documentation for students with lengthy histories of disabling conditions. Finally, guidelines frequently neglected to provide the guidance that evaluators need to generate useful documentation. Benefits and limitations of the recent legal guidance are discussed, and recommendations for testing and enforcement agencies, as well as secondary schools, are provided.